IgG2 antibodies against a clinical grade Plasmodium falciparum CSP vaccine antigen associate with protection against transgenic sporozoite challenge in mice. - Robert Schwenk (PLoS ONE, 2014)
The availability of a highly purified and well characterized circumsporozoite protein (CSP) is essential to improve upon the partial success of recombinant CSP-based malaria vaccine candidates. Soluble, near full-length, Plasmodium falciparum CSP vaccine antigen (CS/D) was produced in E. coli under bio-production conditions that comply with current Good Manufacturing Practices (cGMP). A mouse immunogenicity study was conducted using a stable oil-in-water emulsion (SE) of CS/D in combination with the Toll-Like Receptor 4 (TLR4) agonist Glucopyranosyl Lipid A (GLA/SE), or one of two TLR7/8 agonists: R848 (un-conjugated) or 3M-051 (covalently conjugated). Compared to Alum and SE, GLA/SE induced higher CS/D specific antibody response in Balb/c mice. Subclass analysis showed higher IgG2:IgG1 ratio of GLA/SE induced antibodies as compared to Alum and SE. TLR synergy was not observed when soluble R848 was mixed with GLA/SE. Antibody response of 3M051 formulations in Balb/c was similar to GLA/SE, except for the higher IgG2:IgG1 ratio and a trend towards higher T cell responses in 3M051 containing groups. However, no synergistic enhancement of antibody and T cell response was evident when 3M051 conjugate was mixed with GLA/SE. In C57Bl/6 mice, CS/D adjuvanted with 3M051/SE or GLA/SE induced higher CSP repeat specific titers compared to SE. While, 3M051 induced antibodies had high IgG2c:IgG1 ratio, GLA/SE promoted high levels of both IgG1 and IgG2c. GLA/SE also induced more potent T-cell responses compared to SE in two independent C57/BL6 vaccination studies, suggesting a balanced and productive T(H1)/T(H2) response. GLA and 3M-051 similarly enhanced the protective efficacy of CS/D against challenge with a transgenic P. berghei parasite and most importantly, high levels of cytophilic IgG2 antibodies were associated with protection in this model. Our data indicated that the cGMP-grade, soluble CS/D antigen combined with the TLR4-containing adjuvant GLA/SE warrants further evaluation for protective responses in humans.